Preparation of open‐cell foams from polymer blends by supercritical CO2 and their efficient oil‐absorbing performance. Issue 12 (22nd September 2016) - Fang, Yu‐Wei; Bao, Jin‐Biao; Yan, Hai‐Kuo; Sun, Wei; Zhao, Ling; Hu, Guo‐Hua
Significance: This letter reports on the hydrophobicity and oleophilicity of open‐cell foams from polymer blends prepared by supercritical CO2 . A typical bulk density of the foam is measured to be 0.05 g/cm 3 . The contact angle of the foam with water is determined to be 139.2°. The foam can selectively absorb the diesel from water with the uptake capacity of 17.0 g/g. The foams are technologically promising for application of oil spill cleanup. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4182–4185, 2016